Oral Microbiome and Gingival Transcriptome Profiles of Ligature-Induced Periodontitis. (June 2020) - Ebersole, J.; Kirakodu, S.; Chen, J.; Nagarajan, R.; Gonzalez, O.A.
This investigation evaluated the relationship of the oral microbiome and gingival transcriptome in health and periodontitis in nonhuman primates ( Macaca mulatta ). Subgingival plaque samples and gingival biopsies were collected from healthy sites and at sites undergoing ligature-induced periodontitis. Microbial samples were analyzed with 16S amplicon sequencing to identify bacterial profiles in young (3 to 7 y) and adult (12 to 23 y) animals. The gingival transcriptome was determined with a microarray analysis and focused on the expression level of 452 genes that are associated with the development of inflammation and innate and adaptive immune responses. Of the 396 total operational taxonomic units (OTUs) identified across the samples, 81.8% were detected in the young group and 99.5% in the adult group. Nevertheless, 58 of the OTUs composed 88% of the signal in adults, and 49 OTUs covered 91% of the OTU readouts in the young group. Correlation analyses between the microbiome members and specific gingival genes showed a high number of significant bacteria-gene correlations in the young healthy tissues, which decreased by 75% in diseased tissues. In contrast, these correlations increased by 2.5-fold in diseased versus healthy tissues of adult animals. Complexes of bacteria were delineated that related to specific sets of immune genes, differing in health and disease and in the young versus adult animals. The correlated gene profiles demonstrated selected pathway overrepresentation related to particular bacterial complexes. These results provide novel insights into microbiome changes with disease and the relationship of these changes to specific gene profiles and likely biologic activities occurring in healthy and diseased gingival tissues in this human-like periodontitis model.